2017
DOI: 10.17522/balikesirnef.373421
|View full text |Cite
|
Sign up to set email alerts
|

“Kuvvet ve Enerji” Ünitesine Yönelik Üç Aşamalı Kavramsal Anlama Testi Geliştirme Çalışması

Abstract: -The aim of this study was to develop a valid and reliable three-tier conceptual understanding test aimed to determine middle school students' conceptual understanding towards "Force and Energy" unit. The developed test was applied to 280 students who are studying in 7 th grade of three middle schools located in the central province of Aydın. The three-tier test consisting of a total of 96 questions was used in the study. Expert opinion was consulted for content and face validity of the test. Furthermore, fals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
1
0
2
Order By: Relevance
“…Concept test development studies on various subjects following these test development stages are also found in the literature (Avcı et. al., 2018;Çetinkaya & Taş, 2016;Hasyim, Suwono & Susilo, 2018;Mulford & Robinson, 2002;Özden & Yenice, 2017;Sreenivasulu & Subramaniam, 2013). In the literature, as in this study, there are many studies in which misconceptions were determined with a two-stage test (Avcı et.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Concept test development studies on various subjects following these test development stages are also found in the literature (Avcı et. al., 2018;Çetinkaya & Taş, 2016;Hasyim, Suwono & Susilo, 2018;Mulford & Robinson, 2002;Özden & Yenice, 2017;Sreenivasulu & Subramaniam, 2013). In the literature, as in this study, there are many studies in which misconceptions were determined with a two-stage test (Avcı et.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Bu dersin temel hedeflerinden birisi de öğrencilerin kavramları anlamasını sağlamaktır (Uysal & Bostan Sarıoğlan, 2020;Wood, 2012). Soyut kavramların çoğunlukta olması (Özden & Yenice, 2017) ve öğretim aşamasında somutlaştırmada zorluk çekilmesi (Uysal & Bostan Sarıoğlan, 2020) kavramların öğrenilmesinin önündeki en büyük engellerden bir tanesidir. Fen öğretimi üzerine yapılan araştırmalar incelendiğinde öğrenciler bazı kavramları anlamakta ve tanımlamakta zorlandıklarını (Bakırcı vd., 2016;Uysal & Bostan Sarıoğlan, 2020) ve kavram yanılgılarına sahip olduklarını göstermektedir (Akyıldız, 2020;Alkış Küçükaydın, 2020;Çetinkaya & Taş, 2016;Kocakülah & Turan, 2019).…”
Section: Introductionunclassified
“…Kavram yanılgısı, öğrencilerde yer alan fikirler ya da etiketlemeler ile bilimsel teorilerdeki etiketlemeler arasındaki farklar olarak tanımlanmaktadır (Kaltakçı-Gürel vd., 2015). Bu durum sınıf ortamında bireylerin yeni bilgileri, olguları ya da olayları zihinlerinde yer alan şemalarla ilişkilendiremediğinde yani bir uyumsuzluk yaşandığında ortaya çıkar (Özden & Yenice, 2017). Sözü edilen uyuşmazlık durumu öğrenmeyi engeller.…”
Section: Introductionunclassified